Pengaruh Strategi Generic: Digitalisasi Terhadap Keuntungan Bersaing - Florencia Judith Widyarini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Technological developments support changes in people's behavior, especially the business environment which must adapt to face technological advances. Digitalization, one of the strategies used by companies to develop services and products that can be offered to customers. Digitalization can be analyzed with a focus on competition, data, innovation, value and can become an effective generic strategy. This strategy can support competitive advantage values ​​for companies based on the influence of globalization, consumer expectations, and technological innovations, Digital Transformation, Business Resilience, Continuity, Artificial Intelligence and Analytics, Climate Change and the Environment, Political and Economic Uncertainty, Labor and Skill Migration, Cyber ​​Security, and Inclusion and Diversity In this research, we are looking for a relationship between Digitalization as a way for companies to implement their generic strategy and Competitive Advantage for the company and its competitors. This research uses the Resourced Based View or RBV method and the Market Based View or MBV method to determine this relationship. The results of this paper show that with several studies and theories explained, there is an influence between digitalization strategic and competitive advantage for companies if it can be managed and analyzed well. Keywords: Digitalization, Generic Strategic, Competitive Advantage.